2013
DOI: 10.1016/j.rbmo.2012.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Unusual case of recurrent heterotopic pregnancy after bilateral salpingectomy and literature review

Abstract: Heterotopic pregnancy occurs in up to 1% of pregnancies after IVF and embryo transfer. A case of a 35-year-old woman undergoing IVF treatment who had had previous laparoscopic bilateral salpingectomy due to hydrosalpinges is presented. She had had two heterotopic pregnancies in both tubal stumps in consecutive pregnancies achieved by IVF. The intrauterine pregnancies ended in spontaneous abortions. The possibility of a heterotopic pregnancy needs to be considered when more than one embryo has been transferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 5 publications
1
16
0
2
Order By: Relevance
“…The results of this study showed that multiple-embryo transfer was a risk factor associated with increased incidence of HP ( OR 0.300,95% CI 0.092-0.983; P = 0.037). This nding con rms and expands that of a previous study which believed that the diagnosis of HP must be considered in patients with two or more embryos transferred in a cycle [13]. Therefore, selective singleembryo transfer probably is a preferred choice for a decreased risk of HP.…”
Section: Discussionsupporting
confidence: 85%
“…The results of this study showed that multiple-embryo transfer was a risk factor associated with increased incidence of HP ( OR 0.300,95% CI 0.092-0.983; P = 0.037). This nding con rms and expands that of a previous study which believed that the diagnosis of HP must be considered in patients with two or more embryos transferred in a cycle [13]. Therefore, selective singleembryo transfer probably is a preferred choice for a decreased risk of HP.…”
Section: Discussionsupporting
confidence: 85%
“…In our present study, a total of twenty patients had ipsilateral salpingectomy or even bilateral salpingectomy but this time five had cornual, four had interstitial, and two had tubal stump pregnancy. Moreover, abdominal EP may even be happened on the condition of bilateral salpingectomy which has been reported only four cases with two of ours [ 11 – 13 ]. All together suggested that the risk factors may alter the transport mechanisms and molecules expression systemically.…”
Section: Discussionmentioning
confidence: 79%
“…We further examined the remaining 64 records for eligibility. We excluded 29 studies (from 32 records) for the following reasons: one study (from one record) was still ongoing; six studies (from six records) were not written in a Western language; 14 studies (from 15 records) evaluated fewer than 10 women; six studies (from six records) had insufficient data to evaluate eligibility and the authors did not respond to our electronic attempt to contact them; and two studies (from four records) did not provide IVF results. Therefore, 26 studies (from 32 records) were considered eligible.…”
Section: Resultsmentioning
confidence: 99%